Synthesis and Characterization and evaluation of biological activities of some new pyrroline compounds - Jalil Abed, May (Al-Qadisiyah Journal of Pure Science, 2019)
The chemical preparation of pyrroline compounds through series reactions with acetic anhydride, then iodine in methanol .,periodic acid finally with some derivatives of aniline .,These new derivatives were characterized by I.R,H1NMR , spectra and element analysis data (C.H.N) ,melting point and the yield of the final new compound Key words: Pyrroline compounds, aza sugar, Schiff bases, pyrrol compounds ,heterocyclic compounds.